Highlight selection of radiochemistry and radiopharmacy developments by editorial board - Francisco Alves; Inês F. Antunes; Emiliano Cazzola; Frederik Cleeren; Bart Cornelissen; Antonia Denkova; Jonathan Engle; Alain Faivre-Chauvet; Nic Gillings; Jeroen J. M. A. Hendrikx; Amir R. Jalilian; Nicholas P. van der Meulen; et al. (SpringerOpen, 2021)
Abstract Background The Editorial Board of EJNMMI Radiopharmacy and Chemistry releases a biyearly highlight commentary to update the readership on trends in the field of radiopharmaceutical development. Results This commentary of highlights has resulted in 21 different topics selected by each member of the Editorial Board addressing a variety of aspects ranging from novel radiochemistry to first in man application of novel radiopharmaceuticals. Also the first contribution in relation to MRI-agents is included. Conclusions Trends in (radio)chemistry and radiopharmacy are highlighted demonstrating the progress in the research field being the scope of EJNMMI Radiopharmacy and Chemistry.